Antimicrobial activity of Pediococcus pentosaceus strains against diarrheal pathogens isolated from pigs and effect on paracellular permeability of HT-29 cells - Eunbee Cho; Yoonjeong Yoo; Yohan Yoon (Journal of Animal Science and Technology)
This study aimed to investigate lactic acid bacteria with antimicrobial activities against infectious diarrheal pathogens in pigs and their genetic characteristics. Acid-resistant lactic acid bacteria were examined for bile resistance, pancreatic enzyme resistance, gelatinase and urease activities, and antibiotic resistance. Subsequently, selected isolates were examined for antimicrobial activities against Campylobacter coli, Clostridium perfringens, Escherichia coli, and Salmonella Typhimurium, and their effects on paracellular permeability and the expression of tight junction protein-encoding genes in HT-29 cells were assessed. Whole genome sequencing was performed to identify the genes related to safety and antibacterial activity. Of the 51 isolates examined, 12 were resistant to bile and pancreatin and did not produce gelatinase and urease. Of these 12, isolates 19, 20, 30, 36, and 67 showed tetracycline resistance and isolates 15, 19, and 38W showed antimicrobial activity against infectious diarrheal bacteria. Treatment with isolate 38W signiﬁcantly reduced the paracellular permeability induced by E. coli in HT-29 cells and alleviated the expression of tight junction protein-encoding genes (claudin-1, occludin, and ZO-1) induced by E. coli inoculation. Isolates 15, 19, and 38W were named as Pediococcus pentosaceus SMFM2016-NK1, SMFM2016-YK1, and SMFM2016-WK1, respectively. Bacteriocin-related genes were YheH, ytrF, BceA, BceB, and MccF in SMFM2016-NK1; YheH, ytrF, BceA, BceB, entK, lcnA, MccF, and skgD in SMFM2016-YK1; and YheH, ytrF, BceA, BceB, and MccF in SMFM2016-WK1. SMFM2016-YK1 harbored the tetM gene. These results indicate that P. pentosaceus SMFM2016-WK1 might control diarrheal pathogens isolated from pigs. However, a further study is necessary because the results were obtained only from in vitro experiment.